Instagrammable, Authentic, and Influential: Drivers of Generation Z's Revisit Intention toward KOL-Associated Restaurants in Jakarta's Culinary Hub - Bhatara Richky Batuta; Kevin Gustian Yulius; Dessy Natalia (CV. Media Digital Publikasi Indonesia, 2026)
This study investigates the drivers of revisit intention among Generation Z consumers frequenting Key Opinion Leader (KOL)-associated food and beverage establishments in the revitalized Blok M district of South Jakarta. Grounded in source credibility theory and Bourdieu’s sociological framework, this study examines the structural relationships between KOL Credibility, Perceived Authenticity, Cultural Capital, and Revisit Intention. Data were collected through an online survey of 160 valid Generation Z respondents who met strict screening criteria, including active social media engagement and a recent visit to a KOL-promoted restaurant or café in Blok M. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze the measurement and structural models. The empirical results revealed that the structural model explained 30.6% of the variance in Revisit Intention. Both Cultural Capital (=0.351, p<0.001) and KOL Credibility (=0.240, p=0.001) exert significant positive effects on Revisit Intention, supporting H1 and H3. Conversely, Perceived Authenticity yields no significant direct effect (=0.104, p=0.202), leading to the rejection of H2. Cultural Capital emerged as the most critical driver, demonstrating that for Generation Z, a venue's social currency, digital self-presentation opportunities, and trend alignment heavily outweigh pure authenticity when deciding to return to a venue. Restaurant operators should pivot from focusing solely on conventional authenticity toward creating visually appealing, shareable environments that enable lifestyle participation and trend-relevant marketing. Future research should integrate operational variables, such as food and service quality, to explain the remaining variance.